Controllable synthesis of Fe3O4 nanoflowers: enhanced imaging guided cancer therapy and comparison of photothermal efficiency with black-TiO2. Issue 22 (29th May 2018) - Saeed, Madiha; Iqbal, M. Zubair; Ren, Wenzhi; Xia, Yuanzhi; Liu, Chuang; Khan, Waheed S.; Wu, Aiguo
Abstract : The therapeutic performance of the Fe3 O4 nanoflowers (Fe-NFs) is evaluated and compared with commercially available black TiO2 nanoparticles (b-TiO2 ) Abstract : Photothermal therapy (PTT) has emerged as one of the promising cancer therapy approaches. However, nanoparticles (NPs) which are used for PTT might be biopersistent and potentially toxic. The current research explores the promising use of Fe3 O4 nanoflowers as nontoxic, efficient photothermal, and strong T 2 type magnetic resonance imaging (MRI) contrast agents for imaging-guided photothermal cancer therapy. In this study, a facile solvothermal method is used to fabricate PEG-coated Fe3 O4 nanoflowers with controllable dimensions. Their successful fabrication, the effect of the reaction parameters, and their magnetic properties are investigated in depth. The therapeutic performance of the Fe3 O4 nanoflowers (Fe-NFs) is evaluated and compared with commercially available black TiO2 nanoparticles (b-TiO2 ) under an 808 nm laser. The photothermal therapy efficiency of the Fe-NFs is observed to be better than that of the reported Fe3 O4 nanoparticles. In vitro and in vivo investigation demonstrates that the therapeutic performance of the Fe-NFs is comparable to that of b-TiO2 . Moreover, the Fe-NFs show excellent magnetic properties and magnetic resonance imaging capability to monitor therapeutic performance.